“PENGARUH NORMA-NORMA MASYARAKAT AMERIKA PADA AKHIR ABAD KE 19 TERHADAP TOKOH-TOKOH UTAMA NOVEL THE AGE OF INNOCENCE KARYA EDITH WHARTON” - Amin Khudlori (Jurnal CULTURE (Culture, Language, and Literature Review), 2019)
The Age of Innocence is a novel which tells us about the social condition of the American society at the end of the 19th century. This thesis deals with the American Society’s norms at the end of the 19th century reflected in Edith Wharton’s novel The Age of Innocence. Sometimes the author would like to tell us what really happen in our surrounding through his novel. As a social creature we have to pay attention to our environment. Therefore the main aim of this thesis is to reveal the influence of American society’s norms at the end of the 19th century toward the main characters in Edith Wharton’s novel The Age of Innocence. In writing this thesis, the writer uses the library research method, by which various sources are collected and also used to support the analysis. In approaching the novel, the writer uses the objective and the expressive methods to obtain a deep understanding of the American society’s behavior at the end of the 19th century. The results of the study indicate that the American society at the end of the 19th century still keep their high value. They consider the family honor and respectability above everything. The individual who deviates will obtain punishment that is appropriate with their custom and tradition. However they have to face the fact that the world is changing. Keywords: innocence, family honot, respectabity, social, tradition.